SCHOOL PHYSICAL EDUCATION AND QUALITY OF LIFE: INTERFACES BETWEEN MENTAL HEALTH, LEARNING AND PEDAGOGICAL INNOVATION - Reis, Antonina Guimarães; Dantas, Aparecida José de Sousa; Maciel Lucas, Carlos Magno; de Oliveira, Joelice Conceição; Costa e Costa, José Xavier; de Alvinco, Luana Inácio; da Costa, Maurita Ribeiro; de Souza Santos, Solange; de Ataides, Wedna Lima (Seven Editora, 2025)
This chapter analyzes the contribution of school physical education to promoting students' quality of life and well-being, considering the physical, emotional, and social aspects of human development. The qualitative research was conducted through a literature review and document analysis, based on national legislation and theoretical references in the field. The results show that the discipline promotes the comprehensive development of students by encouraging coexistence, self-esteem, respect for differences, and the development of healthy habits. Furthermore, physical education contributes to combating school dropout, strengthening mental health, and developing socio-emotional skills. The conclusion is that, when well-planned and integrated into educational contexts committed to inclusion and citizenship, school physical education becomes essential in building a school that promotes health, belonging, and quality of life.DOI: https://doi.org/10.56238/sevened2025.029-029